THE EFFECT OF USING COMIC STRIPS ON STUDENTS’ ABILITY IN WRITING SHORT STORY - jeni maghitasarypasaribu jenimaghitasarypasaribu (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract:The aims of this research are to know: 1) The extent of the using comic strips in teaching writing short story, 2) the students’ writing short story ability before and after using comic strips, 3) Whether any significant effect of using comic strips on students’ in writing short story at tenth gradeof SMA Swasta Ma’arif Pasar Sorkam.The population of this research was all of the tenth grade students’ of SMA Swasta Ma’arif Pasar Sorkam which consist of 68 students. Sample were 22 students which taken by using purposive sampling. The research method that used was experimental method with the pre-experimental design by using one group pre-test and post-tes design. To collect the data the writer used observation sheet and test as an instrument. The result of this research: 1) the application of comic strips was 3.71, it was categorized “Very good”, 2) the mean score of the students’ writing short story ability was55 and it was categorized “Bad”. Meanwhile, after using comic strips was 79,5 it is categorized “Good”. The result of data analysis shows that ttest=13.11 while ttable=2.08. it means that ttest is higher than ttable. So, the hypothesis is accepted. It means that, there is significant effect of using Comic Strips on students’ ability in writing short story at the tenth grade students’SMA Swasta Ma’arif Pasar Sorkam in 2020/2021 Academic Year.